Characteristics and diversity of Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease in Vietnam - Tuan-Binh Huynh; Thuy-Dung Mai-Hoang; Tram-Anh Bui-Nguyen; Trinh Thi Phuong Ha; Minh-Duy Phan; Hieu Tran-Van (Aquaculture and Fisheries)
Acute hepatopancreatic necrosis disease (AHPND) is a contagious disease in shrimp with extremely high mortality rate, causing an estimated $23.6 billion loss to the global shrimp industry during 2009–2016. A binary toxin, PirAB, is the causative agent, which is encoded by the pirABvp genes on a virulent plasmid typically found in Vibrio parahaemolyticus. Here, seventeen strains of V. parahaemolyticus were isolated from the Mekong Delta of Vietnam, of which 15 harboured identical pirABvp genes. The remaining two strains, which were PCR-negative for pirAB, and nine positive strains were selected for whole genome sequencing. Multi-locus sequence typing revealed five sequence types (STs), including one novel, that were associated with sites of isolation. A maximum likelihood tree of core genomes revealed that our strains formed three clusters and were closely related to strains from Thailand, South Korea, China, and Philippines. All sequenced strains carried β-lactam (including blaOXA-10 and blaNDM-1) and tetracycline resistance genes, with a range of 3–13 resistance genes. The pirAB-positive strains shared large regions of homology with the prototypical AHPND virulent plasmid. In summary, this work revealed the characteristics of AHPND-causing strains in the Mekong Delta of Vietnam and suggested possible transmission routes among Vietnam and other shrimp farming countries.